Workplace Spirituality, Mental Health, And Turnover Intentions Of Employees In Upscale Hotels In The Accra Metropolis - Appietu Melody Enyonam (University of Cape Coast, 2024)
This study delves into the intricate relationships between workplace spirituality, mental health, employee engagement, and turnover intentions. Furthermore, it seeks to explore how mental health and employee engagement serve as mediators in these connections. The research also examines employees' coping strategies in relation to their mental health. The study utilized a pragmatic research approach and gathered data from 280 employees through self-administered questionnaires and semi-structured interviews with 28 employees working in luxury hotels in Accra. The data was analyzed using both descriptive and inferential statistics for quantitative data and thematic analysis for qualitative data. Structural equation modeling was employed to test the proposed hypotheses. The study found that the mental health of employees was impaired, and they exhibited a moderate level of engagement and turnover intentions. Socio-demographics played a role in employees' experiences with workplace spirituality, mental health, and engagement. Workplace spirituality had a direct influence on mental health and engagement, and indirectly on turnover intentions. Employee engagement and mental health individually mediated the connection between workplace spirituality and turnover intentions. Employees used various coping mechanisms such as problem solving, seeking social support, avoidance, and reliance on mhealth psychosocial support. However, the latter was the most common, and it significantly moderated the relationship between workplace spirituality and mental health. It is imperative for hotel managers to actively foster a strong sense of community among their staff and effectively promote policies, programmes, and practices to ensure a sustainable spiritually thriving work environment.
xvii,358p:,ill